Children and the politics of psychological practice in South Africa: Dawes, A & Donald, D (eds) (1994) Children and adversity: Psychological perspectives on South African research. Cape Town: David Philip. - Burman, Erica (PINS-Psychology in Society, 2026)
This book fulfils many functions at the same time. Not only does it provide a sustained focus on the problems and questions posed by supporting children's development in South Africa, but in so doing it also offers a vital perspective on the dominant approaches to developmental psychology. Each of the fourteen chapters follows a common structure which moves from general analysis of key concepts and methods to consider their relevance and applicability to the South African context. It is this sustained superordinate analytical stance which provides coherence to what is otherwise a very varied book, with chapters ranging across topics as diverse as the relation between health and psychological development (Kalsvig and Connolly), street children (Swart-Kruger and Donald), the emotional impact of political violence (Dawes) and child sexual abuse (Levett). More than this, the discussion of South African research and the particular questions posed by the project of making psychology "relevant" and transformative in moving beyond the ugly shadow of apartheid carries both a specific, and general, set of lessons about the politics of psychological practice. Given this dual address and effects, as structured by my perspective outside South Africa, I will concentrate on the relevance of this book for an international as well as South African audience.